HIV prevention in journalistic information related to Barcelona - Terrón Blanco, José Luis; García Sedó, Ramón (Revista Española de Comunicación en Salud, 2019)
Introduction: The prevention of HIV or AIDS must consist in a strategy that takes into account the biomedical, behavioral and structural approaches to the population that is directed; it is what is called combined prevention (CP). Objectives: This research aims to know if generalist media talk about prevention or PC when they deal with information related to HIV or AIDS and the city of Barcelona. Methodology: The study is an analysis of quantitative content of all the information, regardless of the medium, that speak about HIV or AIDS and Barcelona in the period between September 1, 2017 and September 1, 2018; for this issue, the Kantar Media analysis and monitoring platform has been used from a series of key words. Results: Most of the information does not explicitly talks about prevention (13,82%) and that biomedical approaches prevail, being structurally nonexistent. On the other hand, the analysis of the data shows that the informants do not handle the CP concept. Conclusion: We believe that the media should talk more frequently about prevention, handle the CP concept and deal more often with behavioral and structural approaches.